Removal of kidney fat before chilling--effect on beef tenderloin yield, color and tenderness - de Felicio, P.E.; Kastner, Curtis L.; Allen, Dell M. (American Society of Animal Science, 2008)
Sixteen beef carcass sides were either conventionally dressed or stripped of kidney and pelvic fat before being chilled. After 3 d of chilling at 0 to 4 C, the tenderloins were removed and trimmed of external fat and psoas minor and iliacus muscles. The psoas major muscles were then vacuum packaged and stored 3 more days at 0 to 2 C. Two steaks were then cut 20 cm from the posterior end of each muscle. One steak was subjectively evaluated for color during a 4-d display period (polyvinyl chloride film) at 0 C; the other was used for Warner-Bratzler shear force evaluation. Shear force steaks were frozen until evaluated. No differences (P>.05) in chilled or aged weight, drip loss during aging or thawing and cooking losses were observed between treatments. The conventionally treated beef was lighter colored at d 0 (P<.01) and 1 (P<.05) of display, but no differences (P>.05) between treatments were detected at d 2 and 4. Color change analysis from d 0 through 4 showed less (P<.01) color change for the tenderloins with fat removed. Shear force means were higher (P<.01) for steaks from sides from which the kidney fat was removed before chilling (2.49 kg) than for those treated conventionally (2.26 kg).
Keywords: Food science; Beef tenderloin; Kidney fat; Color; Tenderness; Yield